Difficult diagnosis of cardiac haemochromatosis: a case report. Issue 1 (13th February 2020) - Sudmantaitė, Vaida; Čelutkienė, Jelena; Glaveckaite, Sigita; Katkus, Rimgaudas
Abstract: Background: Primary iron overload cardiomyopathy is an important and potentially preventable cause of heart failure (HF), usually manifesting in the 4–5th decade of life. Patients may be asymptomatic early in the disease with hidden progression of cardiac dysfunction. The challenge of timely detection is an awareness of this systemic disorder and an adequate degree of clinical vigilance. Case summary: A 48-year-old man was referred to the university clinic due to the episode of atrial fibrillation. The specific features of bronze skin and yellow eyes together with a combination of syndromes (cardiomyopathy, cirrhosis, ascites and portal hypertension, diabetes mellitus, and chronic kidney disease) stimulated the testing of iron metabolism markers, which were far above the normal range. Echocardiography and cardiac magnetic resonance (CMR) showed the dilatation of all cardiac cavities and biventricular systolic dysfunction. CMR T2* mapping was consistent with the diagnosis of myocardial and hepatic siderosis. Hereditary Type I haemochromatosis was confirmed by a genetic test. After 6 months of standard HF treatment, chelation therapy with deferiprone and regular phlebotomies imaging tests showed a reduction of ventricular and atrial volumes, an improvement in the cardiac systolic function and a decrease of iron accumulation. Discussion: In this case, complicating syndromes were detected earlier than underlying disease of primary haemochromatosis. Cardiac haemochromatosis should be considered in any patient with unexplained HF, especially in the case of a positive family history, abnormal liver enzymes, endocrinopathies, or evidence of involvement of other organ systems. Screening for systemic iron overload with transferrin saturation and serum ferritin is the first step. Further non-invasive imaging tests should be done to confirm organ involvement.